Stimulation of wind waves generated at deep sea by A tropical storm - RAY, TK (MAUSAM, 1988)
Using a certain pressure profile based on actual observations, horizontal distribution of surface winds are derived which are used for numerical stimulation of waves in deep sea. A quasi-equilibrium of four major forces: pressure gradient, centifugal; surface function and coriolis force have been assumed. Wave charts prepared in the form of polar diagrams can be utilised for operational wave forecasting. Though the solution of the non-linear equations used in the model nee4s the aid of a computer the operational forecaster need to use only simple parameters, like pressure drop at the centre, radius of maximum wind and the speed of movement of the storm. Hindcast of some reliable data indicate high skill score for the model.